(3efjI GdeQjO aj BOGH GdeajO hGdeSJajOs - (3Rjf GdOjf Hf Ydj Hf CMeO GdYGedj GdLHYj , GdnqTpgjO GdKGfj,J (B966 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde HGdbde Yde GdEfSGf eGde jYde hHYO aEf ceGd GdEfSGf EfeG gh HGdYde GdPi jVGgi Hg edGFcI GdSeGA s
(3HChdg agQSs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B193s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs